Evaluation of the engineering geological investigation of the Ayvali dam site (NE Turkey) - Kanik, Mustafa; Ersoy, Hakan (Springer Heidelberg, 2019)
This paper dealt with the geotechnical characterization of the andesitic rock mass cropped out at the Ayvali Dam Site (NE, Turkey) and aimed to determine how well the obtained results corresponded to the situations that emerged after the dam construction was completed. Scan-line surveys, boreholes, and the related field tests were conducted and the laboratory tests were carried out for determination of index, strength, and deformation characteristics of the rock mass. The excavation class of the rock mass was defined as hard ripping, and according to limit equilibrium (LE) and kinematical analyses, the risk of wedge failure could possibly occur at the rock slopes. Additionally, shear strength reduction (SSR) analysis was carried out using finite element (FE) methods to determine whether a circular failure on the right and left slopes could arise or not, and strength reduction factor (SRF) for the rock slopes were determined as 3.4 and 4.9. The different empirical equations pointed out that the ultimate bearing capacity was in the range of 1.4 to 5.8MPa. Thus, water absorption tests pointed out that permeability of the rock mass is about 10(-6)m/s. Based on the results of the numerical analyses, grout curtain depth was assumed to be maximum 60m and 40m at the river bed and the abutments, respectively. The data obtained from the numerical seepage analyses were compared to the conditions showed up after the construction completed, and the applied injection depths showed similarity to those obtained from the numerical analyses.
Keywords: Bearing capacity; Excavatability; Limit equilibrium; Rock slope stability; Numerical analysis; Finite element method